Checking the Pulse of LGBTIQ+ Inclusion and Representation in the Academic Library: A Literature Review. Issue 1 (2nd January 2020) - Matheson, Michelle; Tait, Elizabeth; Reynolds, Sue
ABSTRACT: Libraries aim to meet the needs of the communities they serve inclusive of those from diverse cultural backgrounds, and more recently particularly addressing those who identify as LGBTIQ+. Universities have also begun to focus on building inclusion for LGBTIQ+ students and staff in their communities generally. This review examines the literature as it relates to academic libraries addressing the needs of their LGBTIQ+ users and the provision of LGBTIQ+ information resources to the university community. The literature is discussed under the themes of information needs, service needs and LGBTIQ+ resources and access in collections. Within these themes barriers to meeting LGBTIQ+ users' needs and current recommended responses for academic libraries are also discussed. The review concludes that further evaluation of LGBTIQ+ holdings in academic libraries, and academic libraries' adoption of recommended responses to LGBTIQ+ user needs is warranted. Also identified is the need for an updated examination of LGBTIQ+ users' views on how academic libraries might meet their specific needs.